2007
DOI: 10.1016/j.jinsphys.2007.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Anti-predator defence mechanisms in sawfly larvae of Arge (Hymenoptera, Argidae)

Abstract: Larvae of the sawfly Arge (Hymenoptera, Argidae) are exposed to predators such as ants. Their defence mechanisms, which have been almost unstudied, were investigated by behavioural observations coupled to a morphological approach and by testing the bioactivity of several body parts. Arge larvae raised their abdomen when contacted by Myrmica rubra workers. The ants rarely bit a larva and generally retreated immediately, sometimes without contacting it. Most of those few ants that bit a larva then showed an unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…In addition to this, a slight disturbance to A. xanthogaster larvae results in them curling their posterior body (in a snake-like manner), which may reinforce the effectiveness of the pubescence by producing a 'hedgehog effect'. Similar behaviors have been reported in A. pagana, and they are believed to be anti-predator defense activities (Petre et al 2007).…”
Section: Damage and Life History Of Arge Xanthogastersupporting
confidence: 77%
“…In addition to this, a slight disturbance to A. xanthogaster larvae results in them curling their posterior body (in a snake-like manner), which may reinforce the effectiveness of the pubescence by producing a 'hedgehog effect'. Similar behaviors have been reported in A. pagana, and they are believed to be anti-predator defense activities (Petre et al 2007).…”
Section: Damage and Life History Of Arge Xanthogastersupporting
confidence: 77%
“…Once disturbed, they discharge a viscous oral fluid [39], [40], perhaps as an alternative defensive strategy. In laboratory bioassays, extracts from several isolated body parts of A. pagana and A. pullata proved to be effective as feeding deterrents against ants, and the extracts also rapidly paralyzed feeding ants; both of these bioactivities are ascribed to the action of peptides [32]. The taming of aggressive behavior by ants has been documented also for oligopeptides recently isolated from frogs [6].…”
Section: Discussionmentioning
confidence: 90%
“…However, we started our study from the hypothesis that the toxins would be found also in related but non-pullulating sawfly species. Experiments with extracts from larvae of Arge pagana , a species common on roses in Europe, and from A. pullata , that were tested on ants ( Myrmica rubra L., Formicidae) had caused the latter to show paralyzing effects [32]. These bioassay results indicated that A. pagana contains the toxic peptides just like A. pullata .…”
Section: Introductionmentioning
confidence: 96%
“…caespitum , a message was somehow conveyed to the remaining workers (either by the attacking ant, or by volatile infochemicals within the haemolymph), and few additional attempts were made to attack the D. v. virgifera larva. Because of their incredible effects on their environments (Hölldobler and Wilson 1990; Beattie and Hughes 2002), ants are often the target of haemolymph defences in insects (Boevé and Schaffner 2003; Petre et al. 2007), but laboratory results are seldom reinforced under field situations.…”
Section: Discussionmentioning
confidence: 99%